Crosstalk between AML and stromal cells triggers acetate secretion through the metabolic rewiring of stromal cells - Vilaplana-Lopera, Nuria; Cuminetti, Vincent; Almaghrabi, Ruba; Papatzikas, Grigorios; Rout, Ashok Kumar; Jeeves, Mark; González, Elena; Alyahyawi, Yara; Cunningham, Alan; Erdem, Ayşegül; Schnütgen, Frank; Raghavan, Manoj; et al. (eLife, 2022)
Acute myeloid leukaemia (AML) cells interact and modulate components of their surrounding microenvironment into their own benefit. Stromal cells have been shown to support AML survival and progression through various mechanisms. Nonetheless, whether AML cells could establish beneficial metabolic interactions with stromal cells is underexplored. By using a combination of human AML cell lines and AML patient samples together with mouse stromal cells and a MLL-AF9 mouse model, here we identify a novel metabolic crosstalk between AML and stromal cells where AML cells prompt stromal cells to secrete acetate for their own consumption to feed the tricarboxylic acid cycle (TCA) and lipid biosynthesis. By performing transcriptome analysis and tracer-based metabolic NMR analysis, we observe that stromal cells present a higher rate of glycolysis when co-cultured with AML cells. We also find that acetate in stromal cells is derived from pyruvate via chemical conversion under the influence of reactive oxygen species (ROS) following ROS transfer from AML to stromal cells via gap junctions. Overall, we present a unique metabolic communication between AML and stromal cells and propose two different molecular targets, ACSS2 and gap junctions, that could potentially be exploited for adjuvant therapy.